1993
DOI: 10.1002/ptr.2650070209
|View full text |Cite
|
Sign up to set email alerts
|

Effects of standardized extracts GK501, from Ginkgo biloba L., G115 from Panax ginseng C. A. Meyer, and their combination, gincosan® (PHL‐00701), on the brain levels of biogenic monoamines and on the serum content of prolactin, growth hormone and ACTH

Abstract: In experiments on old (26 months old) rats, we found that the extracts of Punax ginseng (G115), Ginkgo bilobu (GK501) and their combination Gincosan@ (PHL-00701) administered orally at two doses for 7 days induced changes in the levels of biogenic monoamines in some brain regions (frontal cerebral cortex, hippocampus, striatum, hypothalamus and pons). The most characteristic change was the increase produced by the two extracts and their combination in the serotonin level in all brain structures except for pons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

1994
1994
2007
2007

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 10 publications
0
11
1
Order By: Relevance
“…The reported augmentation of 5HT, 5HIAA by EGb 761 (Morier-Teissier et al 1987;Petkov et al 1993) and our observed attenuation of 5HT and 5HIAA levels, and augmentation of NA, DA and their metabolites in various regions of the rat brain, by IGb containing GAC (unpuriÞed extracts) , would seem to reßect, respectively, the anxiogenic-like and anxiolytic manifestation in the animal recipients. The reversible MAO A and MAO B inhibitory activity of the low molecular weight entities from the dried or fresh leaves of Ginkgo biloba has been reported (White et al 1996).…”
Section: Discussionmentioning
confidence: 46%
“…The reported augmentation of 5HT, 5HIAA by EGb 761 (Morier-Teissier et al 1987;Petkov et al 1993) and our observed attenuation of 5HT and 5HIAA levels, and augmentation of NA, DA and their metabolites in various regions of the rat brain, by IGb containing GAC (unpuriÞed extracts) , would seem to reßect, respectively, the anxiogenic-like and anxiolytic manifestation in the animal recipients. The reversible MAO A and MAO B inhibitory activity of the low molecular weight entities from the dried or fresh leaves of Ginkgo biloba has been reported (White et al 1996).…”
Section: Discussionmentioning
confidence: 46%
“…Such specific activity has not been reported in other crude drugs such as Ginkgo biloba L. or Panax ginseng C.A. Meyer (Petkov and Staneva, 1963;Petkov et al, 1993).…”
Section: Discussionmentioning
confidence: 91%
“…Meyer, which also act as regulators in the stress response system (Petkov and Staneva, 1963;Petkov et al, 1993), appear to have a non-specific effect on the DA and NA levels in the striatum and hypothalamus of old rats. Thus, our results suggest that ASH extract may have a different mechanism of action to other analeptics, by preferentially stimulating the striatum and hypothalamus to cope with stress.…”
Section: Discussionmentioning
confidence: 96%